Effect of textile fabric fiber on mechanical properties of cement-sand mortar - M. Musa, N.; M. Lawan, M. (International Journal of Engineering and Technology, 2021)
Cement-sand mortar is widely adaptable material used in construction as a binder for masonry walls or aesthetically for rendering and plas-tering. Fibre-reinforced mortar has been used for many years to increases the mortar’s structural properties. This paper discusses the the influence of textile fabric fibre on the properties of cement-sand mortars. Flexural strength test, compressive strength test and drying shrink-age tests were carried out on mortars made with 0%, 0.5%, 1.0%, and 2.0% textile fabric fibre additive. The tests were conducted at 7, 14 and 28 days and the results obtained showed that addition of textile fabric fibre in cement-sand mortar increases the mortar flexural strength and the mortar compressive strength. While, addition of textile fabric fibre reduces the drying shrinkage it can be concluded that textile fabric fibre can be utilized in cement-sand mortar using 1% optimum content.